2020
DOI: 10.1038/s41598-019-56386-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a Plasmodium falciparum erythrocyte invasion phenotype switch at the whole transcriptome level

Abstract: the central role that erythrocyte invasion plays in Plasmodium falciparum survival and reproduction makes this process an attractive target for therapeutic or vaccine development. However, multiple invasion-related genes with complementary and overlapping functions afford the parasite the plasticity to vary ligands used for invasion, leading to phenotypic variation and immune evasion. Overcoming the challenge posed by redundant ligands requires a deeper understanding of conditions that select for variant pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 91 publications
2
16
0
Order By: Relevance
“…PfMyoA-K764E was confirmed to have a moderate phenotype after RAP treatment under static conditions while suspension conditions lessened the defect, consistent with the hypothesis that the interaction between phospho-S19 and K764 is critical only in stages where gliding is required [25]. The culture conditions that best imitate physiological conditions are not clear, but suspension culture significantly affects invasion phenotypes and adhesin expression [15,53,54]. The recent demonstration that merozoites exhibit actin-dependent gliding [3] might explain why PfMyoA-K764E had a stronger effect on static invasion, if merozoites first tune PfMyoA for gliding before S19 is dephosphorylated to tune the motor for invasion ( Fig 7C).…”
Section: Plos Pathogenssupporting
confidence: 67%
“…PfMyoA-K764E was confirmed to have a moderate phenotype after RAP treatment under static conditions while suspension conditions lessened the defect, consistent with the hypothesis that the interaction between phospho-S19 and K764 is critical only in stages where gliding is required [25]. The culture conditions that best imitate physiological conditions are not clear, but suspension culture significantly affects invasion phenotypes and adhesin expression [15,53,54]. The recent demonstration that merozoites exhibit actin-dependent gliding [3] might explain why PfMyoA-K764E had a stronger effect on static invasion, if merozoites first tune PfMyoA for gliding before S19 is dephosphorylated to tune the motor for invasion ( Fig 7C).…”
Section: Plos Pathogenssupporting
confidence: 67%
“…A transcriptomics study by Nyarko et al, utilizing parasites grown statically or in suspension, revealed that over 200 genes were differentially expressed between conditions, largely representing increases in erythrocyte-binding, rigidity, and invasion-related genes in suspended cultures [32]. These properties enhance P. falciparum cytoadherence; thus, studying these phenomena in a static environment plausibly leads to an underappreciation of genes relevant to successful cytoadherence and immune evasion under the shear stress of the vascular system in vivo.…”
Section: The Contribution Of Rheologymentioning
confidence: 99%
“…The density of PfEMP1 knobs on the RBC surface ( Figure 1B), which mediate sequestration in P. falciparum to avoid physical filtration by the spleen, was reduced fivefold upon adaptation of ex vivo isolates to in vitro culture [31]. Transcription of many P. vivax cytoadherence genes was reduced in vivo in splenectomized Aotus monkeys relative to spleen-intact monkeys, demonstrating that Plasmodium cytoadherence is likely regulated by many factors, including serum lipoproteins [16], rheology [32], and splenic pressure [33].…”
Section: The Contribution Of Rheologymentioning
confidence: 99%
See 2 more Smart Citations